Risk factors for proximal disease extension and colectomy in left‐sided ulcerative colitis. Issue 4 (1st June 2017) - Sahami, S; Konté, K; Buskens, CJ; Tanis, PJ; Löwenberg, M; Ponsioen, CJ; van den Brink, GR; Bemelman, WA; D'Haens, GR
Abstract : Objective: The primary objective of this study was to assess proximal disease extension of ulcerative colitis (UC) over time, with disease behaviour pattern and risk factors for proximal disease extension and colectomy as secondary aims. Methods: All cumulative incident cases diagnosed with UC at the Academic Medical Center between January 1990 and December 2009 were studied. The cumulative risk of colectomy was calculated by Kaplan‐Meier analysis. The Cox proportional hazards regression was used to identify risk factors associated with proximal disease extension and colectomy. Results: In total, 506 UC patients were included with a median age of 33 years (IQR 23–41) at diagnosis. Ninety‐five (18.8%) patients underwent colectomy during follow‐up. Median follow‐up was 10 years (IQR 5–15). Initial disease extent was evaluable in 416 patients, of whom 142 (34.1%) had proctitis, 155 (37.3%) left‐sided colitis and 119 (28.6%) pancolitis. Proximal disease extension was observed in 120 (28.8%) patients during follow‐up (51 proctitis to left‐sided colitis, 39 proctitis to extensive colitis and 30 left‐sided to extensive colitis). Disease behaviour was evaluable in 378 patients, of whom 244 (64.6%) had less than one relapse per year. Younger age at diagnosis (HR 0.98, 95% CI 0.96–0.99) and continuous active disease (HR 2.18, 95% CI 1.27–3.73) were independent risk factors for proximal disease extension. The cumulative risk of colectomy did not change over time between patients diagnosed before and after the year 2000 ( p = 0.341). Continuous active disease (HR 7.05, 95% CI 4.23–11.77), systemic steroids (HR 3.25, 95% CI 1.37–7.71) and cyclosporine treatment (HR 2.80, 95% CI 1.66–4.72) were independent risk factors for colectomy, whereas proctitis at diagnosis (HR 0.43, 95% CI 0.22–0.86) carried a lower risk. Conclusion: In one‐third of UC patients, left‐sided disease at diagnosis will extend proximally during 10 years of follow‐up. Proximal disease extension was not a risk factor for colectomy, but the risk of colectomy is rather determined by continuous disease activity, and use of systemic steroids and cyclosporine.